Pengaruh Content Marketing Dan Brand Awareness Terhadap Keputusan Pembelian Pada Produk Brand Elizabeth Dengan Kepercayaan Konsumen Sebagai Variabel Mediasi (Studi Kasus Perempuan Di Kota Malang) - Ferisca Berlian Juliyanti; Siti Asiyah; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study examines the effects of content marketing and brand awareness on purchasing decisions of Elizabeth brand products, with consumer trust as a mediating variable. A quantitative survey was conducted involving 100 female consumers in Malang City selected through purposive sampling. Data were collected using questionnaires and analyzed with the SEM-PLS method to evaluate direct and indirect relationships among variables. The results indicate that content marketing and brand awareness significantly and positively influence purchasing decisions and consumer trust. Furthermore, consumer trust strengthens the relationship between these variables and purchasing decisions. Therefore, companies are encouraged to improve marketing content quality and enhance brand image to build trust and stimulate purchase intentions. Keywords: Content Marketing, Brand Awareness, Purchase Decisions, Consumer Trust